The Fifth Avenue Artists Society : a novel - Callaway, Joy (Harper, 2016)
"A charming debut about a family of four artistic sisters on the outskirts of Gilded Age New York high society and centered on the oldest--an aspiring writer caught between the boy next door and a mysterious novelist who inducts her into Manhattan's most elite artistic salon which has a seedy underbelly and secrets to hide"--